2013
DOI: 10.1089/aid.2012.0171
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Conserved Gag-Epitopes in Early HIV Infection Is Associated with Lower Plasma Viral Load and Slower CD4+T Cell Depletion

Abstract: We aimed to investigate whether the character of the immunodominant HIV-Gag peptide (variable or conserved) targeted by CD8(+) T cells in early HIV infection would influence the quality and quantity of T cell responses, and whether this would affect the rate of disease progression. Treatment-naive HIV-infected study subjects within the OPTIONS cohort at the University of California, San Francisco, were monitored from an estimated 44 days postinfection for up to 6 years. CD8(+) T cells responses targeting HLA-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
(68 reference statements)
1
15
0
Order By: Relevance
“…Our findings provide a clear demonstration of the broadening of Gag–specific T-cell responses over the course of one year following HIV-1 infection, with this increased immunogenicity associated with lower viral load set point. Our findings are in line with other studies, which have shown that the presence of a high proportion of Gag-specific CD8+ T-cell responses correlates with delayed disease progression [1921, 23, 4648]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings provide a clear demonstration of the broadening of Gag–specific T-cell responses over the course of one year following HIV-1 infection, with this increased immunogenicity associated with lower viral load set point. Our findings are in line with other studies, which have shown that the presence of a high proportion of Gag-specific CD8+ T-cell responses correlates with delayed disease progression [1921, 23, 4648]. …”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, participants with persisting detectable T-cell responses against invariant epitopes, had significantly lower viral load set point values when compared to participants with responses to epitopes containing variant sequences but subsequently lost these responses. These data suggest that persisting Gag-specific T-cell responses, which may be the result of continual invariant viral epitope presentation or the generation of de novo responses to arising variant epitopes, bear the greatest burden on control of early HIV-1 replication and disease progression [19, 24, 49]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Important interplay between protein conservation in HIV-1 and immune targeting has been postulated ( 44 ), including the possibility that immunodominance benefits viral persistence ( 45 ) by preferentially exposing mutable epitopes. It has additionally been suggested that targeting conserved, lower-entropy regions of gag could be associated with a clinical benefit ( 46 ), particularly when targeting the latent HIV-1 reservoir ( 9 ). The primary epitope targeting described here raised the intriguing possibility that the new set of epitopes would be qualitatively different in terms of their conservation.…”
Section: Resultsmentioning
confidence: 99%
“…T cell activity from these studies highlighted the usage of the Gag protein or its components as vaccine candidates. The T cell epitopes on Gag has already been identified [275], with one study reporting that patients whose immune responses targeted the conserved HIV-Gag-epitopes had significantly lower viral load compared to those targeting variable epitopes [276]. For our study, the conserved T cell epitope of Gag protein will be selected to load inside the GNCs to eliciting cell-mediated immunity.…”
Section: Gold Nano-cagesmentioning
confidence: 99%